Life and death full circle - Saraswati, Swami Yogakanti (Munger Yoga Publications Trust, 2020)
As the tile Life and Death - Full Circle suggests, this book looks at the full picture of human experience.Traditions of all times emphasize that a change in attitude is necessary to journey through life with peace and harmony and to prepare for the onward journey past the gates of death. The book concludes with meditations given by Swami Niranjanananda Saraswati which purify one?s intentions and give strong, resilient and positive samskaras, uplifting life after life.
Keywords: Meditation; Yoga